AN EMPIRICAL ANALYSIS OF LOCAL COFFEE BRAND CONSUMPTION IN MALAYSIA - Ismalaili Ismail; Sabiroh Md Sabri2; Ismaanzira Ismail; Nursyamilah Annuar (International Journal of Accounting, Finance and Business, 2024)
The consumption of international coffee and local coffee brands has become increasingly popular in Malaysia, especially among adolescents and the millennial generation. Thus, coffee consumption in Malaysia has grown and flourished in tandem with the needs and demands of the consumers. Hence, the diverse factors influencing consumers towards coffee consumption are relatively significant and considered a major concern in marketing and behavioural studies. Therefore, this study aims to determine the factors influencing the consumption and re-consumption of local coffee brands among Malaysian university students. Quantitatively, this study surveyed 234 respondents by using non-probability sampling which involved all university students in Malaysia. The result reveals that both price and perceived quality have a significant effect on the consumption and re-consumption of the local coffee brand in Malaysia. Based on the result, it is recommended that the owner of the local coffee brand maintain a high product quality through rigorous quality control and effective staff training, while also adopting value-based pricing strategies and offering promotions to remain competitive. Additionally, the owner should emphasize the coffee’s superior quality through targeted marketing campaigns, improve customer experience with excellent service and a welcoming ambience, and engage customers with events and menu diversification. Moreover, this will provide a competitive advantage to their business as consumer trends and behaviours are constantly transformed according to different generations and setting environments.